A web of clues: can ecosystems be profiled similarly to criminals?. (13th July 2021) - Ylönen, Ninni; Rissanen, Matti; Ylä-Kujala, Antti; Sinkkonen, Tiina; Marttonen-Arola, Salla; Baglee, David; Kärri, Timo
The concept of an ecosystem has raised interest in many areas of research over the decades. There is a growing need to model and guide the operations, not just in single companies but also on ecosystem level. To be able to do this, new and better tools are needed. This paper explores the ecosystems of organisations and presents the process for building an ecosystem profile. To understand ecosystems better, managers can utilise ecosystem profiles like criminal investigators utilise criminal profiles. Design science research is used to create the process, and the process steps utilise methods from web farming and social network analysis. The created process is tested with an illustrative case. The process and the profiles created with it can be used by both researchers and managers. The ecosystem profile makes sense of the complex structure and gives data-based insights into the ecosystem under review.